Premature Pubarche, Hyperinsulinemia and Hypothyroxinemia: Novel Manifestations of Congenital Portosystemic Shunts (Abernethy Malformation) in Children - BEREKET, ABDULLAH; HALİLOĞLU, BELMA; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (KARGER, 2015)
Congenital portosystemic shunt (CPSS) is persistence of an anomalous embryological connection of the portal vein with a large vein of the vena cava system. Clinical presentations include neonatal cholestasis, liver tumors, and encephalopathy, but can be variable in timing and symptomatology. We report 2 girls who presented 10 years apart with the same complaint of early pubarche at age 7 years, with inappropriately low DHEAS levels. In addition to hyperandrogenemia (elevated testosterone and androstenedione) and advanced bone age, both had hyperinsulinemia, and hypothyroxinemia. The 2nd case also had symptomatic hypoglycemia. Presentation of CPSS with this combination of findings in prepubertal children has not been reported previously. With further investigations, we proposed novel mechanisms explaining these manifestations. Hyperandrogenemia is caused by decreased hepatic sulfation of DHEA to less active DHEAS due to shunting of DHEA to systemic circulation. Elevated DHEA is then used for synthesis of more potent androgens. Shunting of postabsorbtive glucose from portal to systemic circulation causes early hyperglycemia leading to exaggerated insulin secretion. Insulin bypasses the hepatic metabolism directly entering into the systemic circulation, which results in hyperinsulinemia, then in turn causes late hypoglycemia. Finally, hypothyroxinemia was linked to thyroxin-binding globulin deficiency, which has not been reported in CPSS. (C) 2015 S. Karger AG, Basel
Keywords: Premature pubarche; Hyperinsulinemia; Hypothyroxinemia; Congenital portosystemic shunt; Abernethy malformation; ANASTOMOSIS